Morphometrics Variations of Carpenter Bees Xylocopa confusa Latreille and Xylocopa latipes Drury from Different Habitats in Central Sulawesi - Yulia Windarsih; Manap Trianto (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Habitat is a place for living things to grow and develop. Differences in physical characteristics of habitats within an area can affect the morphometry of an organism. This study aims to provide information related to the morphometric variation of the carpenter bees Xylocopa confusa Latreille and Xylocopa latipes Drury in different habitats in Central Sulawesi. The research was conducted in four types of habitat, namely primary forest, secondary forest, rural areas, and urban areas in January 2019. The collection of carpenter bees useds a sweep net by swinging it around the sampling location. The carpenter bees obtained were then killed in a killing jar for five minutes. The carpenter bees samples were put into a sample bottle based on the type of habitat. Furthermore, the pinning process was carried out using insect needles. The results showed that the physical characteristics of the different habitats could affect the morphometric variations of the carpenter bees Xylocopa confusa and Xylocopa latipes. The size of the body morphometry of carpenter bees is larger in primary forest habitats, while the smallest size of bees is found in urban areas. This research is useful as preliminary data before carrying out the cultivation and conservation process of wood bees considering that their role in nature is very important.